POLIMORFISMO DE LOS MARCADORES MICROSATÉLITES D7S820 Y D16S539 EN UNA MUESTRA DE POBLADORES DE LA PROVINCIA DE YUNGAY, DEPARTAMENTO DE ANCASH” - Martinez y Cols., Rolando (2019)
Recently, STR (Short Tandem Repeat) molecular markers have caused a revolution in the field of Population Genetics and Forensic Genetics due to its high index of probability in the identification of individuals, paternity and family relationships. Nevertheless, the problematic of the identification of human beings with DNA examinations in Peru is limited by the scanty investigation on the determination of allelic frequencies of Peruvian populations. Here we present the result of the genetic variability of microsatellites D7S820 and D16S539 in a population sample of 35 people from the province of Yungay, state of Ancash. The alleles reported here are 9, 10, 11, 12 and 14 for the marker D7S820 and 9, 10, 11, 12 and 13 for the marker D16S539; we found both markers are in genetic balance (Hardy and Weinberg) population sample. There is no significant difference of the allelic frequencies of the sample in study with regard to a population representative sample of Peru for these two markers. In the population analysis, sample from Yungay has more relation with samples from Asian origin; the results corroborate the Asian influence of Native American population.